Amylopectin Regulated Mineralization of Calcium Carbonate and Its Application in Removing of Pb(II). Issue 8 (15th June 2021) - Zhao, Qinjiang; Zhou, Lihong; Du, Jie; Wang, Guanghui; Pei, Xiangjun
Abstract: As an ecological and environment‐friendly building material, sticky rice mortar has attracted the attention of many researchers. Amylopectin is the most important organic matter of it, which can improve the mechanical properties and durability of sticky rice mortar by inducing mineralization of calcium carbonate (CaCO3 ). However, amylopectin induced formation of CaCO3 has not been reported. In this paper, mineralization of CaCO3 induced by gelatinized amylopectin is investigated. For comparison, the different morphologies of CaCO3 are studied in the presence of Mg 2+, Fe 3+ . Moreover, these CaCO3 products with different morphologies are used to clean the waste water. The results indicate that gelatinized amylopectin is conducive to formation of pumpkin‐like vaterite. It forms uniform rod and dumbbell‐shaped calcite in the presence of Mg 2+, form calcite with stepped depressions in the presence of Fe 3+ . The adsorption of Pb(II) can reach extremely high level (1445.86 mg g −1 ) with the rod‐like calcite. Abstract : The hydroxyl group on amylopectin serves as the nucleation site for calcium carbonate. Calcium carbonate with different morphologies is synergistically induced by different metal ions and amylopectin. Pure amylopectin induces the formation of pumpkin‐like vaterite; Mg/amylopectin synergistically induces the formation of rod or dumbbell‐like calcite, and Fe/amylopectin synergistically induces the formation of cubic calcite with stepped depression.